2013
DOI: 10.1590/s0100-204x2013000700011
|View full text |Cite
|
Sign up to set email alerts
|

Adubação com fósforo e potássio para produção e qualidade de sementes de soja

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos da adubação com fósforo e potássio na produção e na qualidade de sementes de soja. Foram realizados experimentos em dois anos agrícolas, em delineamento de blocos ao acaso, em arranjo fatorial 5x3, com cinco doses de fósforo (0, 40, 80, 120 e 160 kg ha -1 de P 2 O 5 como superfosfato triplo), três de potássio (0, 50 e 100 kg ha -1 de K 2 O como cloreto de potássio) e quatro repetições. Foram avaliados: produtividade, número de sementes por planta, número… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…In addition, we can infer over the size of the grain, as well as over its maturity and sanity (Brasil, 2009). In literature, it is reported that the specific mass of the seeds is strongly influenced by the edaphoclimatic conditions and chemical management of the soils (Batistella Filho et al, 2013).…”
Section: When Analyzing Interactions T X L and L X Ymentioning
confidence: 99%
“…In addition, we can infer over the size of the grain, as well as over its maturity and sanity (Brasil, 2009). In literature, it is reported that the specific mass of the seeds is strongly influenced by the edaphoclimatic conditions and chemical management of the soils (Batistella Filho et al, 2013).…”
Section: When Analyzing Interactions T X L and L X Ymentioning
confidence: 99%
“…Batistella Filho et al (2013), in a study on fertilization with phosphorus and potassium for soybean seeds production and quality, concluded that the phosphate fertilization increases yield and does not affect the physiological quality of soybean seeds produced, even in soils with very little phosphorus available. In its turn, fertilization with potassium does not affect the yield nor alter soybean seeds vigor, but can improve germination in soil with medium levels of this nutrient.…”
Section: Attributesmentioning
confidence: 99%
“…Guerra et al (2006) also found that phosphorus applied at the time of sowing increased the vigor, germination, and seedling emergence potential of crops in the field. However, Batistella Filho et al (2013) found that phosphorus fertilization increased the productivity and seed mass for soybean, but did not affect physiological quality. Similar results were observed by Salum et al (2008), who reported that the physiological quality of seeds was favored neither by the phosphorus content in the seed nor its availability in the soil.…”
Section: Introductionmentioning
confidence: 97%